Synthetic Lignan Secoisolariciresinol Diglucoside (LGM2605) Reduces Asbestos-Induced Cytotoxicity in an Nrf2-Dependent and -Independent Manner - Ralph A. Pietrofesa; Shampa Chatterjee; Kyewon Park; Evguenia Arguiri; Steven M. Albelda; Melpo Christofidou-Solomidou (MDPI AG, 2018)
Asbestos exposure triggers inflammatory processes associated with oxidative stress and tissue damage linked to malignancy. LGM2605 is the synthetic lignan secoisolariciresinol diglucoside (SDG) with free radical scavenging, antioxidant, and anti-inflammatory properties in diverse inflammatory cell and mouse models, including exposure to asbestos fibers. Nuclear factor-E2 related factor 2 (Nrf2) activation and boosting of endogenous tissue defenses were associated with the protective action of LGM2605 from asbestos-induced cellular damage. To elucidate the role of Nrf2 induction by LGM2605 in protection from asbestos-induced cellular damage, we evaluated LGM2605 in asbestos-exposed macrophages from wild-type (WT) and Nrf2 disrupted (Nrf2−/−) mice. Cells were pretreated with LGM2605 (50 µM and 100 µM) and exposed to asbestos fibers (20 µg/cm2) and evaluated 8 h and 24 h later for inflammasome activation, secreted cytokine levels (interleukin-1β (IL-1β), interleukin-18 (IL-18), interleukin-6 (IL-6), and tumor necrosis factor alpha (TNFα)), cytotoxicity and cell death, nitrosative stress, and Nrf2-regulated enzyme levels. Asbestos exposure induced robust oxidative and nitrosative stress, cell death and cytotoxicity, which were equally mitigated by LGM2605. Inflammasome activation was significantly attenuated in Nrf2−/− macrophages compared to WT, and the protective action of LGM2605 was seen only in WT cells. In conclusion, in a cell model of asbestos-induced toxicity, LGM2605 acts via protective mechanisms that may not involve Nrf2 activation.